The Blackwell guide to medical ethics - Rhodes, Rosamond; Francis, Leslie 1946-; Silvers, Anita (Blackwell philosophy guides, 2007)
The Blackwell Guide to Medical Ethics is a collection of new essays from acknowledged leaders in the field, designed to guide students through the complexities of the current state of ethics in medicine